2022
DOI: 10.12688/f1000research.74117.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental factors on blood counts of Gambusia affinis caught at Brantas River watershed, Indonesia

Abstract: Background: Contamination of freshwater ecosystems has become a major issue as it threatens public water sources as well as aquatic life. It is important to predict changes in organism health, given a known number of environmental factors and pollutant concentrations, in order to better manage contaminants through biomarker analysis. This study aims to examine the ecosystem health of the Brantas River based on its environmental condition and the hematology profile of Gambusia affinis fish present in the river.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
2
0
1
Order By: Relevance
“…The concentration of glucose in fish blood is influenced by various factors, including metabolism, nutrition, and environmental conditions. The increase in blood glucose in tilapia fish in this study is indicated by the stimulation of catecholamine hormones that occur in the catabolism of glycogen reserves in the liver and muscles, leading to the inhibition of insulin hormone release (Hertika et al, 2021).…”
Section: Blood Glucosementioning
confidence: 67%
“…The concentration of glucose in fish blood is influenced by various factors, including metabolism, nutrition, and environmental conditions. The increase in blood glucose in tilapia fish in this study is indicated by the stimulation of catecholamine hormones that occur in the catabolism of glycogen reserves in the liver and muscles, leading to the inhibition of insulin hormone release (Hertika et al, 2021).…”
Section: Blood Glucosementioning
confidence: 67%
“…Due to the different starvation tolerance of different fish species, there were certain differences in their hematological indicators after starvation. Raise of WBC has been supposed to be helpful in dealing with external pressure ( 29 ). For S. taeniatus , the first raise of WBCs at 7 days of starvation indicated a quick response capacity of the immune system in a short-term starvation state as well as the altered energy allocation in immune system.…”
Section: Discussionmentioning
confidence: 99%
“…El modelo matemático a desarrollar para estudiar la relación teórica del pensamiento científico en el contexto de la especie biomonitor Gambusia punctata (Poey, 1854), se basa en la observación de diferentes variables ambientales y biológicas que influyen en su comportamiento, y la capacidad para regular las poblaciones de larvas de mosquitos (Argota et al, 2020;Wacławek et al, 2022;Madhuri et al, 2024). Estas variables pueden incluir factores como la temperatura del agua, la disponibilidad de alimento, la densidad de población y la presencia de depredadores (Hertika et al, 2022;Eguiraun & Martinez, 2023).…”
Section: Introductionunclassified